2001
DOI: 10.1023/a:1010619223296
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the axillary nodal status on sentinel node mapping in breast cancer and its relevance for technical proceeding

Abstract: Axillary lymph node involvement influences the drainage pattern in breast cancer. Patients with numerous SNs have an increased risk of axillary involvement. A high tracer uptake does not permit the identification of a 'true' SN. A lack of surgical accuracy may lead to pitfalls if the axilla is not screened carefully for all radioactive nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…However, indirect effects of tumor infiltration can manifest as SLS findings. A few previous studies reported a correlation between decreased SLN uptake and increased risk of axillary involvement (13)(14)(15). A reasonable explanation for this phenomenon would be that the lymphatics become progressively infiltrated with tumor cells, blocking the passage of radiotracers (13).…”
Section: Discussionmentioning
confidence: 97%
“…However, indirect effects of tumor infiltration can manifest as SLS findings. A few previous studies reported a correlation between decreased SLN uptake and increased risk of axillary involvement (13)(14)(15). A reasonable explanation for this phenomenon would be that the lymphatics become progressively infiltrated with tumor cells, blocking the passage of radiotracers (13).…”
Section: Discussionmentioning
confidence: 97%
“…Our data collection started in the soon after the establishment of SLNB [21]. Since that time, numerous randomized controlled multicenter trials confirmed the performance and precision of SLNB as a surgical axillary staging procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In this multicentered research approach, we retrospectively analyzed data from 1,214 patients diagnosed with T1-T2 invasive breast cancer undergoing primary surgery at Hanau City Hospital Breast Cancer Center and 2 other cooperating German clinics of obstetrics and gynecology (Hanau City Hospital (n = 880); MainKinzig-Hospital, Gelnhausen (n = 226); St. Vinzenz Hospital, Hanau (n = 168) between 1998 and 2011. The SLNB was evaluated and established at Hanau City Hospital [21] and has rapidly become part of daily routine. Rink et al [22,23] established standardized protocols for SLN detection and found that scintigraphical visualization of SLNs is influenced by metastatic involvement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancer, where axillary nodal drainage is almost always evident,lymphoscintigraphyincreasesthetimeandcostofSLN mapping but does not improve the SLN identification rate [11].Anotheruseoflymphoscintigraphyistoensuresafetyby meansofreducingfalse-negatives [12].Whiledrainagetothe internalmammarynodesissometimesevident,itisnearlyalways accompanied by concomitant axillary nodal drainage [13].Therefore,preoperativelymphoscintigraphymighthave limitedutilityforsurgeonswhodecidenottoremoveinternal mammarySLN [14].…”
Section: Technical Issues In Sln Biopsymentioning
confidence: 99%